Multi-Rice Cooker / Lokman Al-Hakim Abdul Halim - Abdul Halim, Lokman Al-Hakim (2020)
Arroz Enterprise is a Malaysia based and world company that produce multi types of rice cooker for daily used. The company is a world class manufacturer of rice cooker that is set to complete in the highly competitive in manufacture and export of quality rice cooker. Serving in the manufacturing of various designs of rice cooker in the industry, we have produced more than 50 units of products for our clients’ selection. Arroz Enterprise involved in manufacture the product of Multi-rice Cooker. We progressively improve on our product designs, materials as well as the manufacturing process, in order to maximize product quality, reliability and customer satisfaction. The business objective is to achieve a strong branding position as a household name in the rice cooker industry, which is renowned for product quality and service reliability. The company also committed to constantly provide creative, innovative and fresh rice cooker concepts in meeting customers' promotional needs. The business must ensure its items are bearing the logo of large multinational corporate institutions, both locally and multinational level.